2016
DOI: 10.2215/cjn.11741115
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine–Based and Cystatin C–Based GFR Estimating Equations and Their Non-GFR Determinants in Kidney Transplant Recipients

Abstract: Background and objectives eGFR equations have been evaluated in kidney transplant recipients with variable performance. We assessed the performance of the Modification of Diet in Renal Disease equation and the Chronic Kidney Disease Epidemiology Collaboration equations on the basis of creatinine, cystatin C, and both (eGFR creatinine-cystatin C) compared with measured GFR by iothalamate clearance and evaluated their non-GFR determinants and associations across 15 cardiovascular risk factors.Design, setting, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…All three LMW serum proteins have multiple biological functions and prior studies have suggested associations with CVD and CVD risk factors, including obesity, smoking, diabetes, inflammation, dyslipidemia and proteinuria independent of mGFR, although the mechanisms for these associations are not understood. 1, 10, 2022 Cystatin C is a 120 amino acid protein cysteine protease inhibitor, which is generated in all nucleated cells, modulates the immune system, has antibacterial and antiviral activities, and modifies the response to brain injury. 23 B2M is a 100 amino acid protein component of class I major histocompatibility molecules, which is found on the surface of nucleated cells, and is used clinically as a marker for tumor burden in some lymphoproliferative and plasma cell disorders.…”
Section: Discussionmentioning
confidence: 99%
“…All three LMW serum proteins have multiple biological functions and prior studies have suggested associations with CVD and CVD risk factors, including obesity, smoking, diabetes, inflammation, dyslipidemia and proteinuria independent of mGFR, although the mechanisms for these associations are not understood. 1, 10, 2022 Cystatin C is a 120 amino acid protein cysteine protease inhibitor, which is generated in all nucleated cells, modulates the immune system, has antibacterial and antiviral activities, and modifies the response to brain injury. 23 B2M is a 100 amino acid protein component of class I major histocompatibility molecules, which is found on the surface of nucleated cells, and is used clinically as a marker for tumor burden in some lymphoproliferative and plasma cell disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise we explored the serum creatinine data reported in the follow-up file; 74% of tacrolimus patients and 71% of belatacept patients had serum creatinine reported at 1 year posttransplant. 1 year posttransplant estimated glomerular filtration rate (eGFR; calculated using the Chronic Kidney Disease Epidemiology Collaboration equation (23)) was slightly lower among tacrolimus patients compared to belatacept patients (tacrolimus median eGFR 58.5 mL/min/1.73m 2 , IQR 45.9-72.9 versus belatacept median eGFR 62.3 mL/min/1.73m2, IQR 49.1-76.2, ranksum p-value <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of GFR from CysC alone has been demonstrated to be no more accurate than SCr‐based estimates. In a study of renal transplant patients, the eGFR CysC equation was inferior to the performance of eGFR Cr when compared to the gold standard of measured GFR, with more bias and less accuracy . Stevens et al found that after adjusting for measured GFR, CysC was 4.3% lower for every 20 years of age and 9.2% lower for female sex .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that CysC levels are affected by factors other than GFR, suggesting that unmeasured non‐GFR determinants may be similar in magnitude for both CysC and SCr . For instance, CysC is associated with older age, hemoglobin A1c, smoking, past cardiovascular events, uric acid levels, and hypertriglyceridemia . Inflammation is also thought to modulate CysC levels .…”
Section: Discussionmentioning
confidence: 99%